Harry Hastings Pearce Collection. - Pearce, Harry Hastings, 1897-1984. (1949)
The collection contains 2 photographs of Mallacoota, Victoria and portraits of W. Allder Morrison and Rex Ingamells.
Title devised by cataoguer.
Also available online
Donated by Harry H. Pearce.
Associated materials : Papers of Harry Pearce Ms2765.
Poet, folklore historian and collector. His published works include two collections of poetry, "The song of nature and other poems" (1948) and "Dreams and arrows" (1969) and two volumes on the origins of "Waltzing Matilda".
Keywords: Poets -- Australia -- Pictorial works; Mallacoota (Vic.) -- Photographs; Poets